Cuando la empresa se instala, el «diablo» se muda a vivir en los socavones* - Salazar-Soler, Carmen (2010)
The purpose of this paper is to think about the dynamics betweensocial labour relationships and the religious believes in Peruvianmining on the basis of anthropological analysis of data collectedamong Julcani miners (Huancavelica) and Canta artisanal miners(Sierra of Lima) . Julcani miners are observed in two differentsocioeconomic contexts, one of modernization and technologicaldevelopment, and another of mine closure. Canta artisanal minersare also observed in two different periods, one before and the otherafter the installation in the zone of a mineral trade company. It canbe stated that the apparition of «evil» believes in miner’s religioussystem corresponds to the expansion and intensification of capitalistlabour relationships.